2021
DOI: 10.3390/s21144626
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-Driven Analysis and Control of Human-Robot Interactions in Collaborative Applications

Abstract: The utilization of robotic systems has been increasing in the last decade. This increase has been derived by the evolvement in the computational capabilities, communication systems, and the information systems of the manufacturing systems which is reflected in the concept of Industry 4.0. Furthermore, the robotics systems are continuously required to address new challenges in the industrial and manufacturing domain, like keeping humans in the loop, among other challenges. Briefly, the keeping humans in the loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…It was shown that frequency-domain characteristics on different bands had a better prediction rate compared to time-domain features. Human emotions may be taken into account while configuring cobot's settings [14]. For digitizing and analyzing the emotional state of people, this method makes use of electroencephalography (EEG).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that frequency-domain characteristics on different bands had a better prediction rate compared to time-domain features. Human emotions may be taken into account while configuring cobot's settings [14]. For digitizing and analyzing the emotional state of people, this method makes use of electroencephalography (EEG).…”
Section: Introductionmentioning
confidence: 99%
“…As the higher-level intelligent creature, humans represent more complex and diversified needs such as personal security, health, friendship, love, respect, recognition, and so forth. In this regard, humans are highly flexible resources due to the high degree of motion of the physical structure and the high level of intelligence and recognition [129]. When we consider humans and robots work as a team, organizing their needs and getting a common ground is a precondition for human-robot collaboration in complex missions and dynamic changing environments.…”
Section: Human-robot Interactionmentioning
confidence: 99%
“…Some of these studies have explored the use of two robotic arms to hold an object for an operator while they work on it [118]. Other studies have focused on typical assembly tasks where a robot holds an object and the user assembles another part into it [116,117,119,120], or welds a wire into it [115].…”
Section: Indirect Phrimentioning
confidence: 99%